Conflict in the modern world - Smart, Dean; Staton, Richard (AQA/NEAB Modern world revision, 2000)
Pupils will benefit from active revision and reinforcement of acquired skills and knowledge, rather than the traditional 'crammer' style of revision resources which simply offer re-reading of material. Teachers can be assured that the material covered is directly relevant for their topics, as the revision units are closely based on key issues as outlined in the syllabus. Teachers can use the resource by either copying for each pupil, or by selecting and adapting material into their own revision plans. Less able pupils will benefit from the provision of part-completed answers/model answers, and help in developing History skills. This book is written by experienced teachers who can communicate important issues within each topic effectively.